A comparative study of enhancements of critical temperature in Bi-Pb-Sr-Ca-Cu-O superconductors - Tran, Duc; Duong, Nhan Thi Thanh; Le, Tien Minh; Nguyen, Duong Phuc; Nguyen, Man Khac (VNU Journal of Science: Mathematics - Physics, 2017)
In this work, the effects of sintering temperature and Na subtitution on zero critical temperature (T c,0 ) in Bi-Pb-Sr-Ca-Cu-O superconductors were investigated. The Bi 1.6 Pb 0.4 Sr 2 Ca 2 -x Na x Cu 3 O 10+ d bulk samples with x = 0.00 and 0.05 (BPSCCO) were prepared by using the solid state reaction technique at elevated sintering temperatures of 840 and 850 o C. To examine the improvements of structural and superconducting properties of the BPSCCO samples, the X-ray diffraction (XRD), scanning electronic microscope (SEM) and DC resistance versus temperature (R-T) measurements were carried out. The experimental findings exhibit a co-existence of the high T c (Bi-2223) and low T c (Bi-2212) phases in all samples. The estimated volume fraction of the Bi-2223 phase was increased from 71.4 to 75.7%, and the average size of the Bi-2223 grains was enlarged from 4.5 to 9.8 mm as changing the sample preparation conditions. The improved connectivities between the Bi-2223 grains were also obtained by quantitively analyzing the relation between T c,0 and residual resistance ratio (RRR). These improvements were likely to be reasons for the enhancements of T c,0 in the BPSCCO samples.